2015
DOI: 10.1590/s1806-3713201500000014
|View full text |Cite
|
Sign up to set email alerts
|

Study of inhaler technique in asthma patients: differences between pediatric and adult patients

Abstract: Objective: Inhaler technique comprises a set of procedures for drug delivery to the respiratory system. The oral inhalation of medications is the first-line treatment for lung diseases. Using the proper inhaler technique ensures sufficient drug deposition in the distal airways, optimizing therapeutic effects and reducing side effects. The purposes of this study were to assess inhaler technique in pediatric and adult patients with asthma; to determine the most common errors in each group of patients; and to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
1
13
1
3
Order By: Relevance
“…Quanto à justificativa dos passos da técnica inalatória usados pelos artigos, seis utilizaram apenas referências da literatura (11)(12)14,16,(18)(19) ; um estudo, além de usar a literatura, validou a sequência de passos com quatro peritos (13) ; três artigos indicaram a escolha da técnica baseados em revisão de literatura e instruções de fabricantes em bulas (15,20,22) ; um artigo referenciou, além da literatura e instruções de fabricantes, um guideline (17) ; um estudo indicou que a técnica foi desenvolvida a partir de literatura revisada e experiência clínica de especialistas (21) ; e dois artigos referenciaram um guideline (23)(24) .…”
Section: Assessment Of Inhaler Techniques Employed By Patients With Runclassified
See 2 more Smart Citations
“…Quanto à justificativa dos passos da técnica inalatória usados pelos artigos, seis utilizaram apenas referências da literatura (11)(12)14,16,(18)(19) ; um estudo, além de usar a literatura, validou a sequência de passos com quatro peritos (13) ; três artigos indicaram a escolha da técnica baseados em revisão de literatura e instruções de fabricantes em bulas (15,20,22) ; um artigo referenciou, além da literatura e instruções de fabricantes, um guideline (17) ; um estudo indicou que a técnica foi desenvolvida a partir de literatura revisada e experiência clínica de especialistas (21) ; e dois artigos referenciaram um guideline (23)(24) .…”
Section: Assessment Of Inhaler Techniques Employed By Patients With Runclassified
“…Quanto à idade do grupo de aplicação da técnica, verificou-se que três estudos (11,20,24) trabalharam tanto com crianças quanto adultos, um estudo (16) indicou ter aplicado em indivíduos com idade igual ou superior a 14 anos, oito estudos (12)(13)(14)(15)(18)(19)(22)(23) aplicaram em adultos e dois (17,21) em crianças.…”
Section: Assessment Of Inhaler Techniques Employed By Patients With Runclassified
See 1 more Smart Citation
“…7 Despite long time since development, more than 60 years, inhaler technique errors continue to be common among respiratory patients thus reducing the benefits of inhaled medications. 9 Problems with inhaler techniques were recognised shortly after the launch of pMDIs in the 1960s and reviews show that incorrect inhaler technique is unacceptably frequent and has not improved over the past 40 years. 10 Furthermore, incorrect technique has been reported in up to 94% of patients 4,8,[11][12][13] and poor technique was estimated to be prevalent in an average of 50% of cases.…”
mentioning
confidence: 99%
“…18 Studies have shown that with incorrect technique drug delivery to the distal airways is affected, which prevents drug deposition on the respiratory epithelium. 6,9,19 Poor inhaler technique with inhaled corticosteroids and bronchodilators results in loss of their effect, increased reliever use and worsening asthma. 20, Patients are unable to use them properly due to the lack of knowledge and education on proper inhalational techniques.…”
mentioning
confidence: 99%